Curriculum Management in Pesantren-Based Madrasah for Implementing Religious Moderation - Ihsan, Ihsan; Zuhri, Achmad; Annas, Azwar; Noor, Faiq Maqdhum; Muthmainnah, Muthmainnah (QUALITY, 2024)
This study examines the curriculum of pesantren-based madrasahs as a support for the implementation of religious moderation, the traditions of santri (Islamic boarding school students) in practicing religious moderation, and the model of religious practices among santri in pesantren-based madrasahs. The research was conducted in Java, specifically in Madrasah al-Hidayat Lasem, Madrasah Qudsiyyah Kudus, MA KHAS Kempek Cirebon, Madrasah Aliyah Salafiyyah Syafi'iyyah Jombang, and Madrasah Hidayatul Mubtadi'in Lirboyo Kediri. The study used a qualitative method with a post-positivist phenomenological paradigm. Data collection techniques included observation, interviews and documentation. Data analysis was conducted through the stages of data collection, reduction, presentation, and conclusion.The findings indicate that the strengthening of madrasa curriculum is integrated with the values of religious moderation, such as the development of lesson plans and teaching materials that incorporate moderation values. In addition, traditional pesantren books are used as learning resources to inculcate moderate attitudes. Pesantren traditions, such as following the example of elders, preserving local traditions, maintaining a culture of writing, and fostering a scholarly environment, also support the implementation of religious moderation. The synergy between madrasas and interfaith institutions provides opportunities for santri to interact with non-Muslims, promoting patriotism, tolerance, open-mindedness, and anti-fanaticism.Based on these data, the study formulates a model of religious practices for santri that integrates the curriculum and pesantren traditions in promoting religious moderation. This model is expected to serve as a guideline for pesantren-based madrasahs in raising a generation of moderate santri who can contribute positively to national and societal life.